Inverse heat transfer analysis of radiator central heating systems inside residential buildings using sensitivity analysis. Issue 4 (3rd April 2017) - Moftakhari, Ardeshir; Aghanajafi, Cyrus; Moftakhari Chaei Ghazvin, Ardalan
Abstract : In the present study, a novel inverse heat transfer methodology is presented for thermal energy analysis of residential buildings equipped with radiator Heating, Ventilation, Air Conditioning systems using a combination of numerical simulation and sensitivity analysis. With the use of numerical simulation, thermal analysis of building components is simulated in order to calculate temperature field in the computational domain. With inverse analysis technique, we perform the estimation of some thermal parameters with the use of Levenberg–Marquardt and conjugate gradient methods and reported the results with the use of sensitivity analysis inside the building. To confirm the accuracy of numerical simulation, the problem is also simulated with commercial software such as Carrier and Energy-Plus. Then, thermal parameter estimation results of inverse simulation are presented. The present study illustrates the sufficiency of inverse analysis in order to calculate building thermal design parameters with excellent accuracy and precision with the least possible financial design cost.